WNW-ESE-striking Timanian faults in Svalbard - Koehl, Jean-Baptiste P. (2019)
Poster presentation at ARCEx Annual Conference 2019, Sommarøy, Tromsø, 22. - 24. October 2019. https://arcex.no/arcex-2019/.